Krill biomass estimation: Sampling and measurement variability - Bairstow, Fiona; Gastauer, Sven; Wotherspoon, Simon; Brown, C. Tom A.; Kawaguchi, So; Edwards, Tom; Cox, Martin J. (Frontiers in Marine Science, 2022)
Krill are the subject of growing commercial fisheries and therefore fisheries management is necessary to ensure long-term sustainability. Krill catch limits, set by Commission for the Conservation of Antarctic Marine Living Resources, are based on absolute krill biomass, estimated from acoustic-trawl surveys. In this work, we develop a method for determining an error budget for acoustic-trawl surveys of krill which includes sampling and measurement variability. We use our error budget method to examine the sensitivity of biomass estimates to parameters in acoustic target strength models, length frequency distribution and length to wetmass relationships derived from net data. We determined that the average coefficient of variance (CV) of estimated biomass was 17.7% and the average CV due from scaling acoustic observations to biomass density was 5.3%. We found that a large proportion of the variability of biomass estimates is due to the krill orientation distribution, a parameter in the target strength model. Orientation distributions with narrow standard deviations were found to emphasise the results of nulls in the target strength to length relationship, which has to potential to lead to biologically implausible results.